The limit to realize an isolated magnetic single skyrmionic state. Issue 5 (14th January 2019) - Devi, Mayanglambam Manolata; Koshibae, Wataru; Sharma, Gyaneshwar; Tomar, Ruchi; Gaikwad, Vishwajit M.; Varma, Rahul Mahavir; Nair, Maya Narayanan; Jha, Menaka; Sarma, D. D.; Chatterjee, Ratnamala; Ganguli, Ashok Kumar; Chakraverty, Suvankar
Abstract : The limit to realize an isolated single skyrmion is investigated when the particle size approaches to the length scale of the relevant order parameter. Abstract : The physical properties of a nanoparticle change drastically when the particle size approaches the length scale of the relevant order parameter. Herein, we demonstrate the ferrimagnetic ground state of Cu2 OSeO3 nanoparticles, which is otherwise a chiral magnet (including large-size skyrmionic spin texture) in its bulk form. Theoretical studies suggest that such a pure ferrimagnetic ground state in this material (with low Dzyaloshinskii–Moriya interaction to Heisenberg interaction ratio) is possible only in the presence of magneto-crystalline anisotropy energy when the confinement size approaches the skyrmion size (∼50 nm in bulk). These observations suggest the limit to realize an isolated single skyrmion.